2016
DOI: 10.1261/rna.055996.116
|View full text |Cite
|
Sign up to set email alerts
|

The piRNA pathway is developmentally regulated during spermatogenesis in Drosophila

Abstract: PIWI-interacting RNAs (piRNAs) are predominantly produced in animal gonads to suppress transposons during germline development. Our understanding about the piRNA biogenesis and function is predominantly from studies of the Drosophila female germline. piRNA pathway function in the male germline, however, remains poorly understood. To study overall and stage-specific features of piRNAs during spermatogenesis, we analyzed small RNAs extracted from entire wild-type testes and stage-specific arrest mutant testes en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 56 publications
2
49
0
2
Order By: Relevance
“…Notably, though not dependent on Rhi, transcription of Su(Ste) piRNA cluster was shown to span a narrow window from late spermatogonia to early spermatocyte as well (Aravin et al, 2004), likely reflecting the promoter activity that drives Su(Ste) transcription (Aravin et al, 2001). Dynamic expression of piRNA clusters during spermatogenesis is also supported by the study that showed spermatogonia and spermatocytes have distinct piRNA populations (Quénerch'du et al, 2016). In contrast to dynamic localization of RDC complex and cluster expression in testes, previous work depicted a static view of piRNA production in female gonads.…”
Section: Dynamic Expression Of Pirna Clusters During Spermatogenesismentioning
confidence: 78%
“…Notably, though not dependent on Rhi, transcription of Su(Ste) piRNA cluster was shown to span a narrow window from late spermatogonia to early spermatocyte as well (Aravin et al, 2004), likely reflecting the promoter activity that drives Su(Ste) transcription (Aravin et al, 2001). Dynamic expression of piRNA clusters during spermatogenesis is also supported by the study that showed spermatogonia and spermatocytes have distinct piRNA populations (Quénerch'du et al, 2016). In contrast to dynamic localization of RDC complex and cluster expression in testes, previous work depicted a static view of piRNA production in female gonads.…”
Section: Dynamic Expression Of Pirna Clusters During Spermatogenesismentioning
confidence: 78%
“…5 ). The first two (Ago3 and ATP-dependent helicase) play key roles in the Piwi pathway, which regulates the repression of transposable elements during spermatogenesis 42 . The third protein-encoding gene, Testis serine protease, is involved in the sperm/egg interaction.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies suggest that pachytene piRNAs may play a role in eliminating a large number of mRNAs, including meiotic transcripts, in late spermatocytes and early spermatids ( Goh et al, 2015 ; Gou et al, 2014 ; Watanabe et al, 2015 ). Likewise, in Drosophila testes, an RNA precursor expressed in primary spermatocytes from repeats on the Y chromosome is processed into piRNAs that down-regulate expression of the X-linked gene Stellate ( Bozzetti et al, 1995 ; Quénerch'du et al, 2016 ). One possibility is that YTHDC2 may bind and sequester certain pachytene piRNA precursors in early spermatocytes and block them from being processed into mature piRNAs prematurely.…”
Section: Discussionmentioning
confidence: 99%